1991
DOI: 10.3109/08916939109004811
|View full text |Cite
|
Sign up to set email alerts
|

The α-Galactosyl Epitope on Human Normal and Autoimmune Thyroid Cells

Abstract: As much as 1% of circulating IgG in man (the natural anti-Gal antibody) is directed against the alpha-galactosyl epitope, with the structure Gal alpha 1----3Gal beta 1----4GlcNAc-R. The alpha-galactosyl epitope is abundantly expressed on cells of nonprimate mammals, prosimians, and New World monkeys. Its expression is diminished in Old World monkeys, apes, and humans. It has been previously suggested that interaction between anti-Gal and aberrantly expressed alpha-galactosyl epitopes on thyroid cells may contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous studies using porcine hepatocytes treated with α‐galactosidase eliminated the binding of anti‐α‐gal antibodies as well as complement‐mediated lysis of the cells [22,45–47]. However, living xenograft tissues have the potential for constant turnover of membranous proteins resulting in the reappearance of α‐gal epitope within 24 h [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using porcine hepatocytes treated with α‐galactosidase eliminated the binding of anti‐α‐gal antibodies as well as complement‐mediated lysis of the cells [22,45–47]. However, living xenograft tissues have the potential for constant turnover of membranous proteins resulting in the reappearance of α‐gal epitope within 24 h [22].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the specific stimulatory effect of anti-Gal on Graves' disease thyroid cells is not understood as yet, but studies on the structure and expression of the ~I,3GT gene and of other glycosyltransferase genes in these patients may contribute to the understanding of this phenomenon. It is of interest to note that using a highly sensitive radioimmunoassay, we have demonstrated that normal human thyroid cells, like normal red cells, express small amounts of ~-galactosyl epitopes, which apparently are not accessible in vivo to anti-Gal [82]. It may be possible that ~-galactosyl epitopes expression in Graves' disease thyroid cells is modulated so that the epitope becomes accessible to interaction with anti-Gal.…”
Section: Anti-gal and Autoimmune Diseasesmentioning
confidence: 99%
“…Anti-Gal constitutes as much as 1% of circulating total IgG, and 1-4% of total IgM in human sera (2)(3)(4). Although the physiological significance of antiGal is not entirely clear as yet, it has been implicated in autoimmune disease and tumor immunity (5)(6)(7). In addition, anti-Gal Abs are a major barrier to xenotransplantation of pig organs into humans, because hyperacute rejection is initiated by their binding to Gal determinants that are abundantly expressed on porcine endothelial cell glycoproteins and glycolipids (8 -11).…”
mentioning
confidence: 99%